Pengaruh Financial Distress Dan Ukuran Kantor Akuntan Publik Terhadap Auditor Switching - Zavia Mimy Safitri; Siti Asiam (GEMILANG: Jurnal Manajemen dan Akuntansi, 2022)
The aims of this research is to determine the effect of financial distress and size of a Public Accounting Firm on auditor switching in banking companies listed on the Indonesia Stock Exchange for the 2017-2019 period. Based on the sampling technique using the purposive sampling method, 35 companies were obtained. The data analysis used to test this hypothesis is descriptive statistical tests and logistic regression tests using SPSS Version 25. The research results identify that financial distress and size of a Public Accounting Firm have no effect on auditor switching.